Systematic in-depth study on material constitutive parameter identification for numerical cutting simulation on 16MnCr5 comparing temperature-coupled and uncoupled Split Hopkinson pressure bars - Saelzer, Jannis; Thimm, Benedikt; Zabel, Andreas (Journal of materials processing technology, 2022)
A comprehensive systematic comparative study on high-strain-rate tests (Split Hopkinson Pressure Bar), with and without in-situ heating of the specimens and their respective influence on the quality of empirical material models is presented. The determination of material constitutive model parameters is one of the most challenging aspects of the modelling and simulation of machining processes. Chip formation and process forces show a significant dependence on the actual constitutive model and its parameters as well as on the testing method. Typically, the influences of strain, strain rate, and temperature are investigated in separate experiments of quasi-static compression tests and tests, because the most widespread phenomenological constitutive material models (e.g. Johnson–Cook model) neglect interactions between temperature and strain rate. In contrast, the presented work demonstrates, that a coupled experimental approach of strain rate and temperature in the same test increases the quality of such uncoupled material models as well. The authors compared both approaches (separated and in situ temperature-dependent experiments) by determining the constitutive model parameters for AISI 5115 steel samples taken from a single material batch. The parameters are calculated based on a covariance matrix adaptation evolution strategy and applied in identical two-dimensional orthogonal FEM cutting simulations. Process forces and chip thickness values were used for comparison with the machining experiments. The work therefore gives new aspects to decide for a suitable experimental approach when calibrating a constitutive equation.